Femoroacetabular impingement in elite skiers and snowboarders: Return to sports and outcomes after hip arthroscopy - Waltz, R. A.; Comfort, S. M.; Pierpoint, L. A.; Briggs, K. K.; Philippon, M. J. (The American Journal of Sports Medicine, 2022)
Background: Hip arthroscopy has been shown to be an effective treatment for femoroacetabular impingement (FAI) in high-level athletes; however, limited outcome and return-to-play data exist for hip arthroscopy in skiers and snowboarders.